Quantitative Growth Patterns of Scirpus grossus under Fertilized and Unfertilized Peat Soils - Mohammad Moneruzzaman, Khandaker; Md. Sarwar, Jahan; Ali, Majrashi (2014)
Scirpus grossus L. is a principal rhizomatous weed in the rice fields,drainage and irrigation canals, river banks, abandoned rice fields and wasteland in Malaysia. This study describes the clonal growth patterns, mortality number, plant height and flower number of Scirpus grossus under fertilized and unfertilized peat soils. Results: The NPK fertilizer application at 100:30:30 ha-1 resulted in more robust aerial plant growth with ca. 126.75 ramets m-2 (mean dry aerial biomass of 23.2 g plant-1) compared with 117.83 ramets m-2 (16.3 g plant-1) in unfertilized peat soils 24 weeks after planting of the mother plant. Mean ramets mortality was significantly higher in unfertilized peat soils at 30.33 ramets m-2, while in the fertilized paddy soils this was only 8.67 ramets m-2, resulting higher respective net populations in fertilized plot compared to unfertilized plots. Flowering set in earlier among ramets in fertilized peat soils with 51.58 ramets m-2vis-a-vis 38.75 ramets m-2, 24 weeks after transplanting of the mother plant in unfertilized soil. Fertilizer applications to peat soils did not register any significant difference in mean plant height. Conclusion: The time- and space-mediated clonal growth of S. grossus did not register any significant preferential directionality and dispersion of aerial plants irrespective of fertilizer regimes, but rather displaying opportunistic resource capture by aerial and sub-terranean modules.